2021
DOI: 10.1051/0004-6361/202039396
|View full text |Cite
|
Sign up to set email alerts
|

Speed limits for radiation-driven SMBH winds

Abstract: Context. Ultra-fast outflows (UFOs) have become an established feature in analyses of the X-ray spectra of active galactic nuclei (AGN). According to the standard picture, they are launched at accretion disc scales with relativistic velocities, up to 0.3−0.4 times the speed of light. Their high kinetic power is enough to induce an efficient feedback on a galactic scale, possibly contributing to the co-evolution between the central supermassive black hole (SMBH) and the host galaxy. It is, therefore, of paramou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 87 publications
0
25
2
Order By: Relevance
“…Thus UV line-driven winds can reach UFO velocities even when special relativistic corrections (radiation drag) are included. This contrasts with Luminari et al (2021), who conclude that UV line-driving is not capable of generating such high velocity winds. We caution that the two codes make different assumptions about the initial conditions and ray tracing (both of which Q does more accurately and selfconsistently) as well as the opacity (which their code does better), so it is premature to rule out UV line-driving in favour of other mechanisms such as magnetic driving (Blandford & Payne 1982;Fukumura et al 2017) as the origin of UFOs until these factors are all incorporated together.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…Thus UV line-driven winds can reach UFO velocities even when special relativistic corrections (radiation drag) are included. This contrasts with Luminari et al (2021), who conclude that UV line-driving is not capable of generating such high velocity winds. We caution that the two codes make different assumptions about the initial conditions and ray tracing (both of which Q does more accurately and selfconsistently) as well as the opacity (which their code does better), so it is premature to rule out UV line-driving in favour of other mechanisms such as magnetic driving (Blandford & Payne 1982;Fukumura et al 2017) as the origin of UFOs until these factors are all incorporated together.…”
Section: Discussioncontrasting
confidence: 59%
“…We find that the final velocity of the trajectory is independent of the initial velocity and that the wind is able to drastically accelerate (up to 6 orders of magnitude in velocity) over a very small distance ( 1𝑅 g ), which suggests that line-driving can be very effective even when the X-ray shadowed region is very small. We thus find that UV line-driving is sufficient to reproduce the range of observed UFO velocities, as opposed to the findings of Luminari et al (2021). We note that their code assumes an initial density (similar to Q20) rather than calculating it from first principles, and does not include the full ray tracing of both UV and X-rays that are considered here.…”
Section: Can Uv Line-driven Winds Be Ufos?mentioning
confidence: 63%
See 2 more Smart Citations
“…It has been recently reported that the special relativistic effects are of importance for UFO modelling (Luminari et al 2020(Luminari et al , 2021, because the radiation received by the ultra-fast outflows would decrease for increasing outflow velocity. They argued that most of UFO velocities from the literature cannot be reproduced in a radiative-driven scenario within the relativistic treatment, unless the winds are launched at a radii > 50 g , with a velocity up to 0.15 , in a Eddington or Super-Eddington luminosity case.…”
Section: Relativistic Effectmentioning
confidence: 99%